Tributação dos clubes de futebol: a sociedade anônima do futebol - Sacramento, Heber Gomes do (2023)
The purpose of this study is to present the main tax aspects related to football clubs incorporated as non-profit associations, with the analysis of the application of the institute of tax immunity in relation to its assets, income and services. It also brings a general notion about legal rules and tax principles that guide the legal regimes adopted by football clubs, both in the associative model and in the club-company model. It presents the fiscal problems that flood the segment, with abundant legal uncertainty in tax matters, resulting in a systematic increase of fiscal contingencies in the sector. Fiscal and management problems led the legislator to seek a legal model that would contribute to economic development and professional management of football clubs. The failure seen in previous attempts, such as the Zico Law and the Pelé Law, in addition to aid programs on the part of the public power with the installment of tax debts, as in the case of Profut, resulted in the creation of the football companies, created with a special and simplified tax regime. This new tax regime was conceived with the aim of encouraging football clubs to adhere to the new corporate and business model, in addition to being of paramount importance in bringing legal certainty to football clubs, especially in tax matters, representing a unique opportunity for transformation of Brazilian football through a new corporate and tax format